Implementation of information and communication technologies into the business process management system of domestic enterprises in the context of the development of the digital economy - S.V. (Економіка, управління та адміністрування)
The features of the influence of information and communication technologies (ICT) on the transformation of existing business processes of domestic enterprises in the context of the development of the digital economy have been established. Various approaches to the interpretation of the digital economy are analyzed. It has been established that the development of the digital economy in Ukraine is ensured by the formation of the ICT market, and the ICT themselves are an effective tool for improving the management of business processes of enterprises. The dynamics of indicators of the use of information and communication technologies at the enterprises of Ukraine for the last four years has been investigated. It is substantiated that the use of ICT at domestic enterprises at this stage is at the level of formation. Among the reasons of not enough ICT use, it is necessary to highlight the costly investment in ICT and the vulnerable financial position of enterprises, as well as insufficient government support. The basics of the implementation of information and communication technologies in the business process management system are considered and the main information systems for the business process management of the enterprise are analyzed. On the basis of the said above, the opportunities and threats of ICT implementation in the enterprise are identified and reactive measures are proposed. It is concluded that in the realization of new tasks for the implementation of ICT in the business process management system, top management must change approaches to doing business, look for options for optimizing business models, which will lead to the implementation of large-scale organizational and managerial innovations.